(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study was to determine the hand hygiene habits, beliefs, and practice levels of healthcare workers. Materials and Methods: A total of 238 healthcare workers were included in this cross-sectional survey study. The first part of the questionnaire included sociodemographic data and questions about hand hygiene habits, while the second part included questions from the Hand Hygiene Belief Scale (HHBS) and Hand Hygiene Practice Inventory (HHPI). Results: The mean age of the participants was 33.16±8.54 years and 147 (61.8%) of them were male. The majority of the participants were nurses/health officers (n=92, 36.8%). The rate of those who had previously participated in in-service training was 58.4%. The mean HHBS score was 79.79 and the mean HHPI score was 60.08. The mean HHBS score was higher in women than in men (p=0.003). In terms of occupational groups, the mean HHBS score of physicians (p=0.024) and the mean HHPI score of nurses/health officers (p=0.006) were higher. It was determined that the mean HHPI score of the employees working in internal clinics was higher than those working in surgical clinics (p=0.044), while there was no significant difference in terms of the mean HHBS score. The mean HHPI was higher in participants who received in-service training on hand hygiene (p=0.004). Participants who spent <15 seconds on average while washing their hands had a lower mean HHPI than participants who spent a longer time washing their hands (p=0.003). Conclusion: In the study, it was found that the belief in hand hygiene was high and the practice was generally adopted. The fact that employees especially in surgical departments paid less attention to hand hygiene practice was an important problem. Increasing the frequency of in-service pieces of training to increase compliance with hand hygiene and eliminating the preventive factors will be extremely beneficial for reducing nosocomial infections.